Mircea Eliade, Moshe Idel and the new sovoreignist ideologies - Szabo, Lucian-Vasile (Journal for the study of religions and ideologies, 2024)
The disclosures made by Leon Volovici and other researchers about Mircea Eliade’s (and other generation colleagues of his) during his youth led to the discovery of important elements regarding the adherence to the extreme right of the time. Moshe Idel performs an analysis of what remained after these compromising discoveries, trying to outline a portrait of Mircea Eliade, analyzing his entire career and setting the limits of the errors of his youth, investigating with finesse the accusations of anti-Semitism, legionary beliefs and fascism. The purpose of this study is to reanalyze the facts in the context of the epoch, to determine what led to the mass expansion of the concept of Romanianism and of the elitist concept of Romanian exceptionalism. These are the foundation for a study that tries to see to what extent the ideology of the extreme right is found today in Romanian and European politics, where sovereignist and nationalist conceptions are increasingly present.